Intertextual analysis of Viktor Pelevin’s collection of novels Pineapple water for the Fair Lady - Сenys, Tomas (Literatūra, 2019)
This article aims to analyze Viktor Pelevin’s collection of short stories Pineapple water for the Fair lady in the frame of intertextual theory. The analytical method used in this article is based on a typology developed by Gerard Genette. Using this typology, an analysis of transtextual connections present in the text was conducted. The analysis of paratextual connections in the texts made it possible to make an assumption that all the novels are connected by a specular structure. A closer inspection of the intertextual connection and references presented in the text established a connection with certain works of Nabokov. These references to various works of Nabokov allow to view Pelevin’s collection of short stories not as thematically disconnected narratives but as one cohesive entity.
Keywords: Pelevin; Pineapple water for the Fair Lady; quote; intertextuality; paratextuality; Nabokov; specularity